THE INFLUENCE OF PERCEIVED PARENTAL LOVE ON MORAL INTELLIGENCE IN LATE ADOLESCENTS - Wildan, Zaqy; Rohmadani, Zahro Varisna (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2024)
According to the data, there are still many teenagers in the DIY area who have bad behavior. In fact, there are quite a few cases of crime such as klitih, brawls between students, actions against teachers, and various other behaviors that are still being carried out. The purpose of this research is to find out whether there is a relationship between the love given by parents to their children in the process of forming children's moral intelligence. As stated in Bronfenbrenner's theory, the family sphere is very influential in the process of forming a child's behavior. The method used is quantitative. Using a scale distribution for late adolescents aged 18-21 years in DIY. This research found that there is a fairly strong relationship between parental love and children's moral intelligence. Finally, this research provides future input for future researchers to further strengthen this study with different methods.